Postural control and trunk muscle activation in transtibial amputees: A pilot electromyographic study - Huseyin Celik; Mustafa Cem Türkmen; Ali İmran Yalçın; Semra Topuz (PLoS ONE, 2025)
Transtibial amputation affects postural stability, requiring trunk muscle analysis to support balance and rehabilitation. This pilot study aimed to compare trunk muscle activations during postural sway and limits of stability in unilateral transtibial amputees with healthy controls and investigate the relationship between postural control and trunk muscle activations in transtibial amputees. Accordingly, it was hypothesised that transtibial amputees would exhibit altered postural control and trunk muscle activation, both compared to controls and between limbs. This preliminary observational cross-sectional study included a transtibial amputee group (n = 10) and a healthy control group (n = 10). Static and dynamic balance were assessed using a Bertec force platform. Trunk muscle activation was measured bilaterally using the Delsys wireless surface electromyography system while balance was assessed. Subsequently, group differences in postural control and trunk muscle activation were analyzed. Transtibial amputee group showed significantly greater limits of stability distance on the amputated side compared to controls’ non-dominant side (p < 0.05). Additionally, transtibial amputee group exhibited greater lateral postural sway under compliant surface conditions compared to healthy controls (p < 0.05). During limits of stability assesment, external oblique activation was higher on the intact side of transtibial amputee group compared to controls’ dominant side and higher than on the amputated side (p < 0.05). Multifidus activation on the amputated side during compliant surface with eyes open was greater than the intact side (p < 0.05). Longissimus dorsi activation on the intact side in amputee group exceeded controls’ dominant side under all conditions (p < 0.05). Moreover, longissimus dorsi activation on the amputated side was significantly higher than on the controls’ nondominant side during compliant surface with eyes closed (p < 0.05). Preliminary findings highlight disrupted postural control and trunk muscle activation in transtibial amputees, indicating the need for targeted rehabilitation and larger studies.